Cephalometric analysis for the diagnosis of sleep apnea: a comparative study between reference values and measurements obtained for Brazilian subjects - Patrícia Superbi Lemos Maschtakow; Jefferson Luis Oshiro Tanaka; João Carlos da Rocha; Lílian Chrystiane Giannasi; Mari Eli Leonelli de Moraes; Carolina Bacci Costa; Julio Cezar de Melo Castilho; Luiz Cesar de Moraes (Dental Press Editora, 2013)
OBJECTIVE: To verify if the reference values of Sleep Apnea cephalometric analysis of North American individuals are similar to the ones of Brazilian individuals presenting no craniofacial anomalies. The study also aimed to identify craniofacial alterations in Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHS) patients in relation to individuals without clinical characteristics of the disease through this cephalometric analysis. METHOD: It were used 55 lateral cephalograms consisting of 29 for the control group of adult individuals without clinical characteristics of OSAHS and 26 apneic adults. All radiographs were submitted to Sleep Apnea cephalometric analysis through Radiocef Studio 2.0. The standard values of this analysis were compared, by means of z test, to the ones obtained from the control group and these were compared to values from apneic group through Student's t test. RESULTS: There were no significant differences between values obtained from control group and standard values. On the group of OSAHS patients it was observed a decrease on the dimensions of upper airways and an increase on the soft palate length. CONCLUSIONS: The standard values of Sleep Apnea analysis can be used as reference in Brazilian individuals. Besides, through lateral cephalograms it was possible to identify craniofacial alterations in OSAHS patients.